Vaccination Stance in Adolescents and Emerging Adults: the Role of Trust and Knowledge - Lazic, Milica; Pavlović, Ivana; Ilić, Sandra; Damnjanović, Kaja (Psihološka istraživanja, 2023)
The present study investigates the predictive contribution of generalized (toward a relatively large circle of unfamiliar others, e.g., authorities, healthcare system, alternative medicine, etc.) and particularized (to significant others, such as family members and friends) trust and vaccination knowledge in explaining youth’s vaccination intention, as well as the moderating role of vaccination status in the previously mentioned relationships. A total of 835 adolescents and emerging adults (aged 15 to 25, Mage = 18.35, SD = 2.86) from Serbia completed measures of vaccination intention and vaccination status, generalized and particularized trust, and vaccination knowledge. The results of the hierarchical regression analysis showed that prior uptake of vaccine against the coronavirus (vaccination status) was the best predictor of youth's intention to receive the coronavirus vaccine in the future (vaccination intention). In addition, trust in authorities and media, trust in the health-care system and science, and knowledge about vaccines stood out as significant positive predictors, while trust in alternative medicine and God(‘s will) negatively influenced behavioral intention to vaccinate. Contrary to expectations, trust in family and friends did not contribute to the explanation of AEA's intention to get vaccinated. Besides, no moderating role of vaccination status was detected; regardless of vaccination status, the same determinants of AEA’s vaccination intention were registered. The theoretical and practical implications of these findings are discussed in light of the importance of the development of evidence-based national vaccination programs for young people that can have a preventive character in a period of a global confidence crisis.
Keywords: adolescents; vaccination; knowledge about vaccination; generalized trust; particularized trust